Predicting institutional sexual misconduct by adult male sex offenders - Sandler, Jeffrey C. (Criminal justice and behavior, 2013)
Although the Static-99R has been found to be a robust measure of long-term risk to reoffend among adult male sex offenders, few studies have investigated the relationship between Static-99R scores and institutional (i.e., prison) behavior. The current study sought to address this gap in the research by testing the ability of the Static-99 and Static-99R to predict five types of institutional misconduct: (a) sexual, (b) violent (nonsexual), (c) nonviolent (nonsexual), (d) drug-related, and (e) any nonsexual. Results indicate that the Static-99/99R may be useful as predictors of institutional misconduct and, therefore, as a risk classification measure for prisons to protect both staff and inmates and improve institutional environments.